2011
DOI: 10.1175/2010jcli3418.1
|View full text |Cite
|
Sign up to set email alerts
|

Austral Spring Stratospheric and Tropospheric Circulation Interannual Variability

Abstract: The relationship between the October (spring) total ozone column (TOC) midlatitude zonal asymmetry over the Southern Hemisphere (SH) and the stratospheric quasi-stationary wave 1 (QSW1) interannual phase variability is analyzed. Once contributions to the TOC from known global predictors, estimated with a multiregression model, are removed, the residual TOC interannual variability is observed to be dynamically coupled to the stratospheric QSW1 phase behavior. The stratospheric QSW1 interannual phase variability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 33 publications
4
27
0
5
Order By: Relevance
“…Previous studies have revealed the tendency of the Antarctic polar vortex to exhibit an eastward shift in orientation (Huth and Canziani, 2003), in the ozone minimum location (Grytsai et al, 2005;Malanca et al, 2005;Grytsai et al, 2007a, b;Canziani, 2010, 2011;Grytsai, 2011;Hassler et al, 2011) and in the phase of wave 1 in stratospheric temperature (Lin et al, 2010). This eastward shift has been described as possibly connected with a change in tropospheric stationary waves (Grytsai et al, 2007a), tropospheric jet structure (Hio and Hirota, 2002;Agosta and Canziani, 2011) and its strengthening (Wang et al, 2013), and stratospheric ozone and volcanic aerosol concentration (Lin et al, 2010). The quasi-stationary wave (QSW) activity increases typically in austral spring (Randel, 1988), and its enhancement leads to larger vortex asymmetry, a decrease in ozone hole area and net stratospheric ozone loss.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies have revealed the tendency of the Antarctic polar vortex to exhibit an eastward shift in orientation (Huth and Canziani, 2003), in the ozone minimum location (Grytsai et al, 2005;Malanca et al, 2005;Grytsai et al, 2007a, b;Canziani, 2010, 2011;Grytsai, 2011;Hassler et al, 2011) and in the phase of wave 1 in stratospheric temperature (Lin et al, 2010). This eastward shift has been described as possibly connected with a change in tropospheric stationary waves (Grytsai et al, 2007a), tropospheric jet structure (Hio and Hirota, 2002;Agosta and Canziani, 2011) and its strengthening (Wang et al, 2013), and stratospheric ozone and volcanic aerosol concentration (Lin et al, 2010). The quasi-stationary wave (QSW) activity increases typically in austral spring (Randel, 1988), and its enhancement leads to larger vortex asymmetry, a decrease in ozone hole area and net stratospheric ozone loss.…”
Section: Introductionmentioning
confidence: 91%
“…In spring, the ozone distribution in the Antarctic region is asymmetrical with a maximum in the Australian longitudinal sector and a minimum in the Atlantic longitudes (Grytsai et al, 2005;Agosta and Canziani, 2011). Previous studies have revealed the tendency of the Antarctic polar vortex to exhibit an eastward shift in orientation (Huth and Canziani, 2003), in the ozone minimum location (Grytsai et al, 2005;Malanca et al, 2005;Grytsai et al, 2007a, b;Canziani, 2010, 2011;Grytsai, 2011;Hassler et al, 2011) and in the phase of wave 1 in stratospheric temperature (Lin et al, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…It is known that a climatological east-west asymmetry of the Antarctic polar vortex and ozone hole exists with a typical displacement from the South Pole toward the Atlantic sector, 0 • -60 • W (Wirth, 1993;Waugh and Randel, 1999;Grytsai et al, 2007;Agosta and Canziani, 2011). Figure 6 illustrates the changes in the TOC field asymmetry in August under conditions of the strong polar vortex in 2006 (Fig.…”
Section: Zonal Asymmetrymentioning
confidence: 99%
“…2a), indicating that the observed wave is the QSW1. This wave has high amplitude in the stratosphere and dominates by far the flow in the Southern Hemisphere during spring (Agosta and Canziani, 2011;Hartman, 1977;Randel, 1988;Moustaoui et al, 2003b).…”
Section: Observation Of Wave Breaking and Balloon Ejection From The Pmentioning
confidence: 99%
“…The wind along its edge presents little variations in the zonal direction. In spring, however, the SH stratospheric circulation is by far dominated by the quasi-stationary planetary wave with the zonal wavenumber 1 (QSW1) (Geller and Wu, 1987;Wirth, 1991;Bowman, 1993;Agosta and Canziani, 2011;Hartman, 1977;Randel, 1988;Moustaoui et al, 2003b). The QSW1 causes the vortex to be displaced from the pole or even split.…”
Section: Introductionmentioning
confidence: 99%